Blunted serum 25(OH)D response to vitamin D3 supplementation in children with autism. (2nd July 2020) - Kerley, Conor P.; Elnazir, Basil; Greally, Peter; Coghlan, David
Abstract : Introduction: Data suggest a potential role for vitamin D in autism spectrum disorder (ASD) prevention and treatment. It is likely that the serum response to vitamin D supplementation contributes to its effectiveness. Multiple factors affect serum vitamin D 25(OH)D response to supplementation. Methods: We conducted post-hoc analysis of two double-blind, randomized, placebo-controlled trials (RCT) of vitamin D3 supplementation, one RCT involving children with ASD and another involving children with asthma. Both trials were conducted in the same geographic location (Dublin, Ireland, 53°N), conducted over Winter season and utilized the same vitamin D3 dose (2000 IU/day). Results: We included 18 children with ASD and 17 children with asthma. There was no significant difference in 25(OH)D or age at baseline, however, BMI was significantly lower in ASD ( P = 0.03). Compliance with vitamin D supplementation was high in both trials. Despite a significantly longer intervention period (20w vs. 15w; P < 0.0001), ASD children had a significantly lower absolute increase (+26 vs. +45 nmol/l) in 25(OH)D ( P = 0.04). Conclusions: Despite similar demographics, children with ASD had a lower increase in 25(OH)D levels with supplementation. Potential mechanisms include altered absorption/metabolism as well as well genetic factors. Clinical and research work relating to vitamin D is ASD should measure 25(OHO)D response to supplementation to assess therapeutic doses.